STUDI FENOMENOLOGI : PENGALAMAN KELUARGA MERAWAT PASIEN PASCA STROKE DENGAN GANGGUAN MOBILISASI - Kartika Sari; Wasisto Utomo; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Stroke is a functional disorder of the brain caused by decreased blood supply to the brain due to blockage (ischemic stroke) or spontaneous rupture of blood vessels (hemorrhagic stroke). Stroke can cause some effects such as disruption of mobilization. Post-stroke patients who experience physical mobilization barriers will have difficulty in performing daily activities and need help from family. A strong relationship between the family and the health status of family members can determine the role of the family when facing the problem. The family is also a vital support system or major system support for individuals. The purpose of this study was to explore the family experience of treating poststroke patients with impaired mobilization. The research is a qualitative research using phenomenology study approach. The number of participants in this research were four people taken by purposive sampling technique. The data of research was collected by in-depth interviews using semi-structured question. The results of this research have six themes: 1) first experiences of families with post-stroke patients, 2) post-stroke patient home care, 3) family coping, 4) the obstacles in caring the patient in post-stroke, 5) post-stroke patient management, 6) the impact of the post-stroke to the family. The conclusion of the research is that families should be able to choose coping appropriate to the situation or problems encountered during the post-stroke patient's home treatment with disruption of mobilization, because by choosing the right coping strategy will help the family undergo patient care and will be a motivation for patients and family members who care. The results of the research are expected to assist families in caring for poststroke patients with mobilization disorders, so that families can overcome the difficulties encountered during treating post-stroke patients with mobilization disorders because the family is a support system for the recovery of patients.Keyword: mobilization disorder, phenomenology study, post-stroke